Exact and numerical solitons with compact support for nonlinear dispersive K(m,p) equations by the variational iteration method - İnç, Mustafa (Elsevier, 2007)
We implemented a variational method for approximating the solution of the nonlinear dispersive K(m,p) type equations. By using this scheme, the explicit exact solution is calculated in the form of a quickly convergent series with easily computable components. To illustrate the application of this method, numerical results are derived by using the calculated components of the variational series. The obtained results are found to be in good agreement with the exact solution. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: nonlinear dispersive K(m,p) equations; variational iteration method; Lagrange multiplier